On seeing-off the first graduate s of Lithuanian school for young mathematicians - Apynis, Antanas; Stankus, Eugenijus; Šinkūnas, Juozas (Lietuvos matematikos rinkinys, 2000)
The curriculum of Lithuanian school for young mathematicians and its realization is reviewed.